IDEAL CONDITION OF THE CRIMINAL JUSTICE SYSTEM IN AN EFFORT TO DERADICALIZE THE CRIMINAL ACT OF TERRORISM TO ACHIEVE SUBSTANTIAL JUSTICE - Taufiq, Muhammad (DERECHTSSTAAT, 2017)
The purpose of this study is to examine how law enforcement and prevention efforts and Deradicalisation of terrorism acts in the perspective of Human Rights, Local Wisdom, and realizing a Substantial Justice Criminal System in Indonesia. The approach method used in this scientific work is the normative juridical approach method. With the presentation of data qualitatively. This study emphasizes that the law as a means of law enforcement in Indonesia, especially in the enforcement of Law on Combating Terrorism Crime. The result of this research is that it can be concluded that local wisdom in communal society can be used as media to optimize and strengthen the role of society in countering radical groups and terrorists can be an option to minimize the negative effects caused by the approach of security (hard approach).Â